PERAN KETERAMPILAN KONSELOR (COUNSELOR SKILL) SEBAGAI PROBLEM SOLVING PADA PERMASALAHAN REMAJA (STUDI LITERATUR) - FITRIANA, HERLINA (Al-Tazkiah : Jurnal Bimbingan dan Konseling Islam, 2019)
Adolescence is a period of transition and period of searching for identity. In these times a person will experience an emotional instability. Sometimes to get emotional balance, there will be an internal conflicts. Conflicts in adolescence have various forms, ranging from mild delinquency to overreaching and even in the category of crime such as free sex, drug use, alcohol and many more. The role of the counselor in helping to cope with these problems is very necessary. The counselor's success in the counseling process is inseparable from the personality and skills possessed by the counselor. The counselor's personality is a balancing fulcrum between the knowledge of behavioral dynamics and therapeutic skills. If the fulcrum is strong, the knowledge and the skills will work in balance. In addition to personality factors, the skills possessed by the counselor are also very important in supporting the success of the counseling process. The purpose of writing this article is to examine the literature review related to counselor skills as a problem solving in cope with adolescent problems. The results of the study provide an illustration to us that basically all approaches in the counseling process are not the most right or the wrong one. All approaches have their advantages and weaknesses. Not all approaches to counseling can be used in a case, there are some cases that only require one or two approaches depending on the problems that faced by the client.